2020
DOI: 10.1002/ente.202000777
|View full text |Cite
|
Sign up to set email alerts
|

A Piezo Smart‐Braid Harvester and Damper for Multifunctional Fiber Reinforced Polymer Composites

Abstract: The past decade has seen the rapid development of wearable electronics, wireless sensor networks (WSNs), and self‐powered implantable sensors. However, these devices usually require a continuous source of power supply to operate safely and accurately while having the least reliance on conventional battery systems—due to the recharging/maintenance burdens of batteries. Vibration‐based piezoelectric energy harvesting (PEH) from environment, man‐made machinery, and human body movements seems to be a promising sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…The measurement results showed that the peak value of output voltage was 380 mV and the power density of 29.62 µW/cm 3 could be produced by compressing or bending the single-fiber nanogenerator, which was about 1559% higher than previously reported piezoelectric textiles. Razavi et al [97] fabricated another single-fiber nanogenerator (Figure 5c). This structure featured a number of PVDF yarns braided around copper and coated by copper wires; it achieved excellent mechanical performance and piezoelectric properties.…”
Section: Principle and Structure Of Pengsmentioning
confidence: 99%
“…The measurement results showed that the peak value of output voltage was 380 mV and the power density of 29.62 µW/cm 3 could be produced by compressing or bending the single-fiber nanogenerator, which was about 1559% higher than previously reported piezoelectric textiles. Razavi et al [97] fabricated another single-fiber nanogenerator (Figure 5c). This structure featured a number of PVDF yarns braided around copper and coated by copper wires; it achieved excellent mechanical performance and piezoelectric properties.…”
Section: Principle and Structure Of Pengsmentioning
confidence: 99%
“…Compared with the traditional inorganic piezoelectric materials, piezoelectric polymers (e.g., poly­(vinylidene fluoride) (PVDF) and its copolymer counterparts) generally show the merits of light weight, high flexibility, good compatibility, and processability. Therefore, they are the ideal alternatives to the traditional inorganic piezoelectric materials. Accordingly, PVDF-based piezoelectric sensors have been successfully fabricated by different techniques, such as melt extrusion, injection molding, casting, electrospinning, and so on. Among them, electrospinning, as a versatile technique, can prepare a piezoelectric nanofiber with higher β crystal content owing to in situ electric poling and mechanical stretching. Nevertheless, for most PVDF piezoelectric sensors fabricated by electrospinning, complicated post-treatments such as electrode arrangement and packaging are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…[ 28 ] These devices often require a continuous power supply to operate safely and accurately, while with minimal reliance on conventional battery systems. [ 29 ] Single‐source energy harvesters that convert solar, thermal, or kinetic energy into small smart electronic devices and wireless sensor networks into electricity have been developed for decades. When a single energy source is insufficient to generate the required electricity, a multi‐source energy collection is indicated.…”
Section: Introductionmentioning
confidence: 99%